Atomic structural details of a protein grafted onto gold nanoparticles. Issue 1 (December 2017) - Giuntini, Stefano; Cerofolini, Linda; Ravera, Enrico; Fragai, Marco; Luchinat, Claudio
Abstract The development of a methodology for the structural characterization at atomic detail of proteins conjugated to nanoparticles would be a breakthrough in nanotechnology. Solution and solid-state NMR spectroscopies are currently used to investigate molecules and peptides grafted onto nanoparticles, but the strategies used so far fall short in the application to proteins, which represent a thrilling development in theranostics. We here demonstrate the feasibility of highly-resolved multidimensional heteronuclear spectra of a large protein assembly conjugated to PEGylated gold nanoparticles. The spectra have been obtained by direct proton detection under fast MAS and allow for both a fast fingerprinting for the assessment of the preservation of the native fold and for resonance assignment. We thus demonstrate that the structural characterization and the application of the structure-based methodologies to proteins bound to gold nanoparticles is feasible and potentially extensible to other hybrid protein-nanomaterials.